The Significance of Organizational Culture, Work Spirit, and Job Satisfaction on Employee Performance at the Public Broadcasting Institution (LPP) TVRI South Sulawesi - Nurul Insani; Muhammad Ikram Idrus; Dg. Maklassa Dg. Maklassa (Green Publisher Indonesia, 2024)
This study aims to analyze and explain the influence of organizational culture, work spirit and job satisfaction on employee performance at the public broadcasting institution TVRI South Sulawesi. This type of research is quantitative with data collection techniques using questionnaires through 140 respondents and analyzed using multiple linear regression techniques and partial hypothesis testing is carried out. The results of the study indicate that organizational culture, work spirit and job satisfaction each have a significant influence on employee performance at the Public Broadcasting Institution (LPP) TVRI South Sulawesi with a 95% confidence level.